Face Pain Scale and Borg Scale compared to physiological parameters during cardiopulmonary exercise testing - Morishita, S.; Tsubaki, A.; Hotta, K.; Inoue, T.; Qin, W.; Kojima, S.; Fu, J. B.; Onishi, H. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: The aim of this study was to investigate the differences between the Face Pain and Borg Scales for rating of perceived exertion (RPE) during cardiopulmonary exercise testing (CPET) in healthy adults, and their relationships with work rate (watts), heart rate (HR), oxygen uptake (VO2), and minute ventilation (VE). METHODS: In this prospective observational study, two experiments were conducted. In Experiment 1, 77 healthy adults were randomly assigned to either the group using the Face Pain Scale (19 men, 18 women) or using the Borg Scale (21 men, 19 women) for the RPE during CPET. In Experiment 2, 40 healthy adults (20 men, 20 women) used both the Face Pain and Borg Scales for the RPE during CPET. In both experiments, CPET was performed on ramp protocols with incremental increases in the work rate by 20 watts/minute. Their responses in terms of watts, HR, VO2, VE, and RPE (assessed using the Face Pain Scale or Borg Scale) were recorded each minute. RESULTS: There were significant relationships between the two scales and all physiological variables during CPET in 74 out of the 77 participants in Experiment 1 and in all subjects in Experiment 2 (P<0.05). The correlation coefficient of the Face Pain Scale with respect to the physiological parameters was slightly lower than that of Borg Scale in both experiments (P<0.05). The Face Pain Scale had a significant correlation with the Borg Scale during CPET in Experiment 2 (P<0.05). CONCLUSIONS: The Face Pain Scale may be useful for determining the intensity of exercise in healthy adults, similar to the Borg Scale.